California County Planning Commissioners Association Conference-Lake Tahoe - Watkins, Howard::::::::: (1983)
State Senator Ray Johnson, Association's annual banquet entertainment with magician Louis Falenga Secretary-Treasurer Marjorie Shields and husband on right